2020
DOI: 10.1080/17512786.2020.1727354
|View full text |Cite
|
Sign up to set email alerts
|

The Turncoat Phenomenon: Role Conceptions of PR Practitioners Who Used To Be Journalists

Abstract: For a long time, Dutch parliamentary journalists have shown an interest in migrating to the "other side" and becoming political PR professionals or spokespersons. The Dutch term used by journalists for colleagues who make this switch is "overloper" (turncoat). It is a term with a clear negative connotation, which says a lot about how journalists view the field of public relations. The relationship between journalism and public relations has received much academic attention, revealing a rather strong antagonism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In their last paragraph under the heading ‘Types of Work’, they mention some of the other jobs performed by freelancers, such as copy editors and photographers, adding that the freelancers ‘should expect to take public relations (PR) assignments at some point in their self-employment career’ ( 2018 : 7). With this statement Massey and Elmore echo the customary binary of journalism and public relations ( Fröhlich et al, 2013 ; Kester & Prenger, 2021 ), but do not take up the now more common instances of sponsored content or advertorial writing ( Carlson, 2015 ; Coddington, 2015 ; Serazio, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In their last paragraph under the heading ‘Types of Work’, they mention some of the other jobs performed by freelancers, such as copy editors and photographers, adding that the freelancers ‘should expect to take public relations (PR) assignments at some point in their self-employment career’ ( 2018 : 7). With this statement Massey and Elmore echo the customary binary of journalism and public relations ( Fröhlich et al, 2013 ; Kester & Prenger, 2021 ), but do not take up the now more common instances of sponsored content or advertorial writing ( Carlson, 2015 ; Coddington, 2015 ; Serazio, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Autonomy is a key element of journalists’ self-concept (Kester and Prenger, 2021). In line with former studies, the respondents knew what they could communicate about and what they could not (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…They can select their own stories and present them in the way they want to (Deuze, 2005;Hallin and Mancini, 2004;Kovach and Rosenstiel, 2021;Mellado, 2021;Anderson and Schudson, 2019;Waldenstr€ om et al, 2019). The decrease in autonomy is perceived as especially problematic when journalists move to the "dark side" (Kester and Prenger, 2021). In a study on journalists working in public relations, Koch et al (2020) identified three types of brand journalist self-concept, namely quasi-journalists, hybrids and corporate writers, finding that some of the respondents maintained a strong journalistic self-concept while others did not.…”
Section: Journalism As a Profession And Journalistic Self-conceptmentioning
confidence: 99%
See 2 more Smart Citations